Fish diversity of Tembeling and Pahang rivers, Pahang, Malaysia - Abdul Rashid, Zulkafli; Asmuni, Mustafa; Azmai, Mohammad Noor Amal (Pensoft Publishers, 2015)
This study aim to provide an updated checklist of fish species inhabiting Tembeling and Pahang rivers, Pahang, Malaysia. A total of 4,834 fish belonging to 10 orders, 64 genera, 25 families and 82 species were collected from both connected rivers. Cyprinidae present the highest number of fish species registered herein, followed by Bagridae, Pangasiidae and Siluridae. The most common fish species were Cyclocheilichthys apogon, followed by Barbonymus schwanefeldii, Hypsibarbus wetmorei, Amblyrhynchichthys truncatus and Puntioplites proctozysron. A total of nine introduced fish and four endangered fish species were also recorded from this study. This checklist adds knowledge on the fishes inhabiting both rivers, which could be useful for the planning of fisheries activities and fish conservation of the rivers in the near future.